2021
DOI: 10.1186/s13287-021-02200-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of peripherally administrated neural crest stem cells on pain and spinal cord changes after sciatic nerve transection

Abstract: Background Severe peripheral nerve injury significantly affects patients’ quality of life and induces neuropathic pain. Neural crest stem cells (NCSCs) exhibit several attractive characteristics for cell-based therapies following peripheral nerve injury. Here, we investigate the therapeutic effect of NCSC therapy and associated changes in the spinal cord in a sciatic nerve transection (SNT) model. Methods Complex sciatic nerve gap injuries in rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…For example, in a rat sciatic nerve model, Lv et al found that NCSC promoted regeneration and reconstruction of a transected sciatic nerve by seeding NCSC in a PLLA electrospun conduit [140]. More recently, NCSC-laden nerve scaffolds were shown to attenuate nerve sciatic transection pain, improve motor function recovery, and protect spinal cord from glial activation [141]. An important consideration is whether transplanted cells have the potential to elicit inflammatory host immune responses.…”
Section: Advancements In Stem Cell Technology and Nerve Repairmentioning
confidence: 99%
“…For example, in a rat sciatic nerve model, Lv et al found that NCSC promoted regeneration and reconstruction of a transected sciatic nerve by seeding NCSC in a PLLA electrospun conduit [140]. More recently, NCSC-laden nerve scaffolds were shown to attenuate nerve sciatic transection pain, improve motor function recovery, and protect spinal cord from glial activation [141]. An important consideration is whether transplanted cells have the potential to elicit inflammatory host immune responses.…”
Section: Advancements In Stem Cell Technology and Nerve Repairmentioning
confidence: 99%
“…Moreover, the formation of synapses and regeneration of axons could be promoted after stem cell transplantation via the interactions between stem cells and the surrounding tissues. This could also modify the injury site microenvironment and accelerate the growth of the neural axon by generating some neurotrophic growth factors [28]. Transplanted stem cells could also enhance the myelin formation around neural axons, both newly grown and previous ones, by differentiating into gliocytes and oligodendrocytes.…”
Section: Therapeutic Mechanisms Of Stem Cellsmentioning
confidence: 99%
“…Enhanced function symptoms performed hypersensitivity (nonstimulating pain and increased pain sensitivity), while dysfunction symptoms were mainly manifested as tactile and thermal hyposensitivity, and in the advanced stages, patients may even develop complete loss of sensation [ 6 ]. Among the various neuropathic symptoms, cardiac autonomic neuropathy may result in sudden death, abnormal pain seriously affects the patient's comfort, and pain insensitivity leads to the high risk of burns, trauma and ulcers, eventually leading to amputation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that stem cell transplantation partially repaired damaged neurons and delayed the progress of amyloidosis in the treatment of Alzheimer's disease [ 8 ]. Stem cell treatment also promoted the repair of the injured plane in the treatment of transverse nerve injury caused by trauma [ 7 ]. Importantly, compared with other treatment options, stem cell transplantation can reverse neuropathy, which may be associated with high proliferation and differentiation of stem cells; also the specific mechanism remains unclear [ 12 ].…”
Section: Introductionmentioning
confidence: 99%